PERANCANGAN ARSITEKTUR ENTERPRISE MONITORING PBB DI DESA AWILUAR KECAMATAN LUMBUNG MENGGUNAKAN ZACHMAN FRAMEWORK - Robby Fathulmubin Lukman; Maulana Sidiq; Tuti Rohayati (Jurnal Mahasiswa Sistem Informasi Galuh, 2026)
The Land and Building Tax (PBB) is an important revenue source for village development. In Awiluar Village, Lumbung District, PBB monitoring is still performed manually, making data processing, reporting, and real-time tracking difficult. This study designs an enterprise architecture for a PBB monitoring system using the Zachman Framework, based on observations, interviews, and document reviews. The results include business process models, design diagrams, and a network topology suited to the village’s needs. Applying the Zachman Framework provides a comprehensive system overview, facilitates information management, and improves monitoring efficiency.